Relasi Hukum Dan Moral Dalam Sistem Penegakan Etika Penyelenggara Pemilihan Umum Di Indonesia - Dewi, Sofi Rahma (Acta Law Journal, 2022)
Legal positivism overshadows the legal system applied in Indonesia in the legal concept of "rechtsstaat", according to valid legal positivism is a formalized law, law is not a social or moral fact that must be avoided by non-legal elements. The doctrine of positivism was born as a rejection of the school of natural law, they rejected the laws of nature because they were considered too metaphysical and idealistic, thus failing to provide legal certainty. On the other hand, if positivism separates law from morality, the current of natural law argues that society, morality, and positive law are inseparable. Mainstream positivism is interesting to study together with the Indonesian socio-cultural context in a system that supports the ethics of election organizers. Using normative legal methods, this study examines how legal and moral relations support the ethical system of Indonesian election organizers. The results of this study concluded that in the ethical enforcement system of Indonesian election organizers, the relationship between law and morality in the context of legal substance shows an integrative relationship, and there cannot be attached a constitutional difference between morality and law. Even the value in Election Organizer Regulation Number 2 of 2017 and DKPP Regulation Number 3 of 2017, DKPP Regulation 3 is amended by DKPP Regulation Number 3 of 2019 as a formal law that is taken into account as a moral right. However, in its implementation in the field, the integrative relationship becomes an independent whole, giving rise to two different institutions, each independent in its handling, regarding ethical violations and lawlessness.